Knowledge, Attitude, and Practices of Health Professionals Working in A Major Health Care System Regarding Social Determinants of Health (SDOH) and Community Health Workers (CHW’s) - Khan, Muhammad Nausherwan; Azhar, Erum; Zain, Areeba; Bowman, Meredith Root; Ahmed, Natasha Tahir; Khan, Muhammad Arslan; Caswell, Leigh; Waheed, Abdul (Archives of Clinical and Biomedical Research, 2023)
Introduction: Social Determinants of Health (SDOH) play a key role in impacting the health outcomes of any population. Community Health Workers (CHW’s) play an important role in health promotion, disease prevention, and management of chronic illnesses. This study aims at exploring the knowledge, attitude, and practices of healthcare professionals towards CHWs to fully integrate them for the mitigation of SDOH. Materials and Methods: A cross-sectional study utilizing an anonymous survey questionnaire across 4 clinical sites was carried out from June 2016 to November 2017 in a major healthcare system (Presbyterian) in Albuquerque, New Mexico. Descriptive statistics (means, standard deviations, and proportions) were collected. Categorical variables were analyzed using Chi-squared and Fisher’s exact test; a p-value of <0.05 was considered statistically significant, using SAS 9.4 statistical software. Results: Almost half of the health professionals had no knowledge about the social determinants of health. Almost a quarter of the health professionals did not know the role of CHWs in healthcare, however, 100% of the respondents across all clinic and practice locations and regardless of their role or scope of the practice believed that greater involvement of CHWs would improve patient outcomes. Conclusion: There is a knowledge deficit among health care providers about the social determinants of health (SDOH).More educational and teaching opportunities on SDOH and CHWs to all health professionals should be provided to all health professionals so the clinical team can help manage SDOH in addition to providing clinical care.